Crime and the Legalization of Recreational Marijuana - Davide Dragone; Giovanni Prarolo; Paolo Vanin; Giulio Zanella (Institute of Labor Economics (IZA), 2017)
We provide first-pass evidence that the legalization of the cannabis market across US states may be inducing a crime drop. Exploiting the recent staggered legalization enacted by the adjacent states of Washington (end of 2012) and Oregon (end of 2014) we find, combining county-level difference-in-differences and spatial regression discontinuity designs, that the legalization of recreational marijuana caused a significant reduction of rapes and thefts on the Washington side of the border in 2013-2014 relative to the Oregon side and relative to the pre-legalization years 2010-2012. We also find evidence that the legalization increased consumption of marijuana and reduced consumption of other drugs and both ordinary and binge alcohol.
Keywords: K23; K42; 330; cannabis; recreational marijuana; crime